Prognostic significance of p27 in colorectal cancer: a meta-analysis and bioinformatics analysis - Zou, Jing; Wang, Dong; Yin, Gaoping; Lu, Kexiang; Chang, Kaibin; Li, He (Frontiers in Oncology, 2024)
BackgroundIn the past, numerous investigations have delved into the influence of p27 (p27kip) on the prognosis and clinicopathological characteristics of colorectal cancer (CRC), yielding conclusions that are not universally statistically significant, thus rendering the discourse rather contentious.MethodsWe collected available articles published before August 2024 and extracted data to analyze the association between the expression of p27 and the prognosis and clinicopathological features of CRC. In addition, we used Gene Expression Profiling Interactive Analysis (GEPIA), University of Alabama at Birmingham’s Cancer Data Analysis Portal (UALCAN), and the Human Protein Atlas (HPA) to validate our results.ResultsThrough an extensive examination of four prominent databases, a total of 21 original articles encompassing a cohort of 3,378 patients were identified. The findings indicated that a low expression of p27 could lead to shorter overall survival (OS) [hazard ratio (HR) = 0.44, 95% confidence interval (95%CI) = 0.31–0.61, Z = 4.89, p = 0.000] and disease-free survival (DFS) (HR = 0.40, 95%CI = 0.28–0.59, Z = 4.75, p = 0.000). In addition, a low expression of p27 predisposed tumors to the right colon [odds ratio (OR) = 0.61, 95%CI = 0.46–0.82, Z = 3.32, p = 0.001] and limited tumor differentiation (OR = 0.56, 95%CI = 0.41–0.77, Z = 3.62, p = 0.000), but had no effect on TNM staging (OR = 0.80, 95%CI = 0.52–1.22, Z = 1.05, p = 0.295), lymph node metastasis (OR = 0.90, 95%CI = 0.25–3.28, Z = 0.16, p = 0.876), and tumor size (OR = 0.94, 95%CI = 0.54–1.65, Z = 0.21, p = 0.835). The results from GEPIA and UALCAN showed that p27 had no effect on TNM staging, lymph node metastasis, DFS, and OS; moreover, there was no expression difference between tumor tissues and normal tissues. The findings from the HPA indicated that there was lower expression of p27 in tumor tissues compared with normal tissues.ConclusionAlthough inconsistent results were reached with the bioinformatics analysis from this meta-analysis, it was confirmed that a low expression of p27 can adversely affect the prognosis of patients with CRC and make a meaningful impact on a part of the clinicopathological features in the meta-analysis with abundant data. In the future, predicting the prognosis of patients with CRC and guiding treatment might emerge as a significant objective.